Can Employee Share Option Scheme Improve Firm’s Performance? A Malaysian case study - Long, Choi Sang; ., Ajagbe Akintunde Musibau (Information Management and Business Review, 2013)
This paper examines the impact of employee share option schemes (ESOs) on one company in Malaysia. It is hoped that the findings of this study will be useful to companies who wish to adopt such schemes and to market regulators. The financial and operational indicators were studied for a total period of 11 years (five pre-ESOs and five post ESOs). In line with the findings of other studies done in Malaysia, Singapore and other countries, it has been found that the deterioration in financial performance was not arrested by ESOs. The operation and productivity of the company showed no improvement postESOs. This study concludes that ESOs do not motivate employees and the objectives of the ESOs were not fulfilled. This study also finds that the beneficiaries of ESOs are the majority shareholders/managers and the losers are the minority shareholders. Based on these results, it will be difficult to make a case for the usefulness of ESOs.